(untitled) (Thành phố Hồ Chí Minh, 2009)
The fastest man on four wheels, Ricky Bobby (Will ferrell) is one of the greatest drivers in Nascar history. A bifg, hairy American winning machine, Ricky has everything a dimwitted dararredevil could want: a luxurious mansion, a smokin' hot wife (Leslie bibb) and all the fast food he can eat. But Ricky's turbo-changed lifestyle hits an unexpected speed bump when he's bested by flamboyant Euro-idiot Jean Girard (Sacha Baron Cohen, TV's "Da Ali G Show") and reduced to a fear-ridden wreck. Losing his wife and job to best bud and fellow fool, Cal Naughton, Jr. (John C.Reilly), Ricky must kick some serious asphalt if he's to get his career back on the track, beat Girard and reclaim his fame and fortune. 'Cause as Ricky Bobby always says, IF YOU AINT FIRST, YOU'RE LAST!
Keywords: Motion pictures,Phim điện ảnh